PENEGAKAN HUKUM KEPEMILUAN UNTUK PEMILU BERMARTABAT - Junaidi Ahmad; Agmar Media (Jurnal Sosial Humaniora Sigli, 2021)
The notion of popular sovereignty and the rule of law must go hand in hand. As a characteristic of a modern state, democracy is manifested through general elections with integrity. Law enforcement and election justices are the principles and formulas for elections with integrity. The independence of the organizing agency, transparency, and accountability will foster people's trust as the holder of the right to vote. Elections with integrity give birth to legitimacy for every representative elected in the voting booth. Maintaining the people's right to vote through law enforcement is the absolute responsibility of all stakeholders when the General Election takes place. Keywords:Law Enforcement, Election, Dignified